2007
DOI: 10.1055/s-2007-967171
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Volatile Oil from Ginger Rhizomes (Zingiber officinale), its Fractions and Isolated Compounds on the 5-HT3 Receptor Complex and the Serotoninergic System of the Rat Ileum

Abstract: A contribution of the volatile oil from ginger rhizomes (Zingiber officinale Roscoe) on inhabiting the 5-HT3 receptor complex had been shown. In the present study a possible interaction of some compounds of the volatile oil with the 5-HT3 receptor system expressed in N1E-115 cells and with the serotoninergic system of the rat ileum was investigated. The volatile oil was obtained by steam distillation and fractionated using a silica gel column resulting in five fractions. Compounds of the fractions were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…They can also cause nervous system disorders (convulsions, disorders of balance [26] In addition, the compounds are active on the smooth muscles of the ileum part of rat intestine. They act by inhibiting the 5-HT3 receptors of the serotoninergic system of the murine intestinal cells [83]. In rats, β-pinenes exert an antinoxious effect on the supra spinal parts, but not on the spinal cord itself [28].…”
mentioning
confidence: 99%
“…They can also cause nervous system disorders (convulsions, disorders of balance [26] In addition, the compounds are active on the smooth muscles of the ileum part of rat intestine. They act by inhibiting the 5-HT3 receptors of the serotoninergic system of the murine intestinal cells [83]. In rats, β-pinenes exert an antinoxious effect on the supra spinal parts, but not on the spinal cord itself [28].…”
mentioning
confidence: 99%
“…Some asserted that the antiemetic effect results from the inhibition of serotonin receptors in the gastrointestinal system and the central nervous system 'vomiting center' , as well as the inhibition of vasopressin which causes a reduction in tachygastric activity [25][26][27][28][29] . There are various active ingredients found in the ginger including gingerol, shogaol, and galanolactone, which produce antiemetic effects using difference mechanisms [30][31][32] . The ginger used for NVP should be obtained from Zingiber officinale, and not from other types of ginger with a different Latin name such as the ones that come from African or Thailand, due to the differences in the balance of chemical constituents 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been found that Ginger might interact with anticoagulants and anti-platelets as ginger itself has an anticoagulant effect 29,[32][33][34][35][36] . Furthermore, it is known to cause gastrointestinal irritation and is contraindicated in patients with or have a history of gallstones as it stimulates secreting bile 37 .…”
Section: Controlmentioning
confidence: 99%
“…Moreover in rat colon it has been shown that ginger extract decrease motility [18]. While in the rat ileum it has spasmolytic effect [19], in guinea pig ileum ginger improves motility [20]. Isolated gingerols and shogaols have been shown to modify gastric motility in animal experiments [21].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated gingerols and shogaols have been shown to modify gastric motility in animal experiments [21]. Although it was demonstrated that ginger accelerated gastric motility [12], about lower gastrointestinal region there are paradoxical information [18][19][20]. It seems that the effect of ginger in gastrointestinal tract motility, depends to organ and spices and different in upper and lower part of gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%